2021
DOI: 10.20883/medical.e503
|View full text |Cite
|
Sign up to set email alerts
|

Rare diseases – a challenge for the medical world

Abstract: The diagnosis and treatment of rare diseases have improved significantly in recent years. The length of the diagnosis, which from the point of view of patients and their caregivers was considered the "Achilles' heel" of the healthcare system, has significantly shortened in many cases. Nevertheless, as research shows, there is still much to be done regarding the knowledge of rare diseases among healthcare professionals. The processes of diagnosis and treatment, as well as their organisation, should be redefined. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Moreover, this research supports findings from other countries that have shown that both medical students and healthcare professionals lack training and experience on RDs and that many problems of RD patients result from their negative experiences with healthcare system (40)(41)(42)(43)(44). For example, several Polish studies conducted among nursing, physiotherapy and medical students and practicing physicians and nurses showed that they possess insufficient knowledge about RDs and do not feel prepared to care for such patients (28,29,(45)(46)(47)(48)(49). Also research conducted in Spain (50,51) and Belgium (52) showed that most physicians do not possess adequate knowledge on RDs and rarely use Orphanet or other reliable sources on the Internet.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, this research supports findings from other countries that have shown that both medical students and healthcare professionals lack training and experience on RDs and that many problems of RD patients result from their negative experiences with healthcare system (40)(41)(42)(43)(44). For example, several Polish studies conducted among nursing, physiotherapy and medical students and practicing physicians and nurses showed that they possess insufficient knowledge about RDs and do not feel prepared to care for such patients (28,29,(45)(46)(47)(48)(49). Also research conducted in Spain (50,51) and Belgium (52) showed that most physicians do not possess adequate knowledge on RDs and rarely use Orphanet or other reliable sources on the Internet.…”
Section: Discussionsupporting
confidence: 84%
“…Secondly, while taken individually RDs are rare or ultra-rare, when combined they affect a significant number of people, as approximately 6–8% of the world’s population suffer from them. This means that between 300 and 350 million people worldwide are affected, including 27–36 million in the European Union (EU) [ 5 ] and 2.3–3 million in Poland [ 3 , 6 – 8 ]. Thus, because RDs affect a very large number of people they constitute an important medical and social challenge and an urgent public health issue [ 4 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, patients/caregivers reported more problems with low-Phe products than with Phe-free formulas, but it was less difficult for most patients to adhere to the diet during the lockdown than before. Assuming that this was the reality, that is, due to objective or subjective causes, e.g., pandemic-related stress and not exclusively the patients’ feelings, it could have impacted their diet and deteriorated problems related to vitamin and mineral intake already observed in the pre-pandemic period [ 13 , 14 , 15 , 16 , 17 ]. Moreover, these issues together with general changes in food consumption observed during the pandemic could have influenced energy and metabolic balance, increasing overweight and obesity problems observed in patients with PKU [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%